Implantation of a diffractive trifocal intraocular lens: one-year follow-up - Mojzis, Peter; Majerova, Katarina; Hrckova, Lucia; Piñero, David P (Journal of cataract and refractive surgery, 2015)
PURPOSE: To evaluate the visual, refractive, contrast-sensitivity, and aberrometric outcomes during a 1-year follow-up after implantation of a trifocal intraocular lens (IOL). SETTING: Premium Clinic, Teplice, Czech Republic. DESIGN: Prospective case series. METHODS: This study included eyes of patients having cataract surgery with implantation of the trifocal IOL model AT Lisa tri 839MP. Distance, intermediate (66 and 80 cm), and near (33 and 40 cm) vision; contrast sensitivity; aberrometric outcomes; and the defocus curve were evaluated during a 12-month follow-up. The level of posterior capsule opacification (PCO) was also evaluated. RESULTS: In 120 eyes (60 patients), 1 month postoperatively, an improvement was observed in all visual parameters (P ≤ .03) except corrected near and intermediate visual acuities (both P ≥ .05). From 1 month to 12 months postoperatively, small but statistically significant changes were observed in uncorrected and corrected distance and near visual acuities (all P ≤ .03) and in uncorrected intermediate visual acuity (P = .01). In the defocus curve, no significant differences were found between visual acuities corresponding to defocus levels of -1.0 diopter (D) and -2.0 D (P = .22). The level of ocular spherical aberration decreased statistically significantly at 6 months (P < .001). Ocular and internal higher-order aberrations increased minimally but significantly from 6 to 12 months postoperatively (P < .001). The mean 12-month PCO score was 0.32 ± 0.44 (SD). Four eyes (3.3%) required neodymium:YAG capsulotomy. CONCLUSION: The trifocal IOL provided complete and stable visual restoration after cataract surgery during a 12-month follow-up, with good levels of visual quality. FINANCIAL DISCLOSURE: No author has a financial or proprietary interest in any material or method mentioned.
Keywords: Pseudophakia; rohovkové aberace; Capsule Opacification; Adult; senioři; aberometrie; Corneal Wavefront Aberration; Aged; Male; Aberrometry; lidé; nitrooční čočky; zraková ostrost; lidé středního věku; Humans; Prosthesis Design; Middle Aged; Lenses, Intraocular; citlivost na kontrast; protézy - design; Lens Implantation, Intraocular; mužské pohlaví; pseudofakie; Contrast Sensitivity; následné studie; dospělí; refrakce oka; prospektivní studie; Phacoemulsification; ženské pohlaví; implantace nitrooční čočky; Visual Acuity; Follow-Up Studies; Refraction, Ocular; Female; fakoemulzifikace; zkalení zadního pouzdra čočky; Prospective Studies